Kajian Aspek Keselamatan Jalan Terhadap Jalan Daerah Kabupaten Tana Toraja Untuk Mendukung Kegiatan Ekonomi Dan Pariwisata - Patiroi, Andi (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
Infrastructure development play important role in order to develope the tourism sector. Tana Toraja is a potential region to be developed on tourism sector. One of the problem is insufficient of road infrastructure for both connectivity and accesbility issues. This study aimed to give recommendations of road safety as to be technical consideration for Directorate General Highways to budgeting State Budget (APBN) in regional road in tana Toraja. This study was conducted on 5 link of regional roads that were considered as the potential to support the tourism sector. Qualitative approach is used as methodology trough data collection and information for analysis. The results show that all of the road link observed has geometric problems (i.e substandard road) and potential to cause accidents, such as road grade more than 10%, width of lane less than 3 meters, inadequate road shoulders, small radius of curve, and hazard objects on the side of the road side. Recommendations to fullfillment road standards must be applied for both the design stage and construction stage.